PENGARUH PROBLEM BASED LEARNING (PBL) TERHADAP AKTIVITAS DAN HASIL BELAJAR SEGIEMPAT PADA SISWA KELAS VII SMPN - Fergiyanti, Mira; Masjudin, Masjudin (Media Pendidikan Matematika, 2016)
This research aimed to the influence of Problem Based Learning (PBL) toward Student Activity and Learning outcomes At Seventh Grade Students of SMPN 4 Lingsar In Academic Year 2015/2016 in absorbing and the materiel given by the teacher with looking observation sheets and student learning outcomes using problem based learning method. problem based learning was the problem giving method relating with daily activity to students then students according to group looked for solution alternative to solve the problem. The type of this research is experiment research. The design of this research is quasi experiment with â€œpretest-posttest group designâ€. The population of this research was the seventh grade students at SMPN 4 Lingsar which were four classes. Sample interpretation technique was determined with purposive sampling, so that this was acquired seventh-A class as experiment class and seventh-B class as control class. According to the result of data analysis was acquired student activity score in experiment class that was 82, 75% with so active category and activity score in control class was 53% with active enough category. Statistic test result (t-test) showed that tcount was 4,878 on the significant (two directions) that were 0,000 with 39 free degrees and it was acquired table test 1,684. Because t count was 4,878 > ttable (1,684) and significant level was 0,000 and Î± was 0, 05 (sig< Î±). Therefore it can be concluded that noel hypothesis (Ho) was rejected and alternative hypothesis was accepted or it can be concluded that there is the significant difference after given treatment, that means there is the influence of Problem Based Learning (PBL) toward Student Activity and Learning outcomes At Seventh Grade Students of SMPN 4 Lingsar In Academic Year 2015/2016.